The dying process : patients' experiences of palliative care - Lawton, Julia, 1969- (Routledge, 2000)
"Taking as its focus a highly emotive area of study, The Dying Process draws on the experiences of day care and hospice patients to provide a forceful new analysis of the period of decline prior to death." "Placing the bodily realities of dying very firmly centre stage and questioning the ideology central to the modern hospice movement of enabling patients to 'live until they die', Julia Lawton shows how our concept of a 'good death' is open to interpretation. Her study examines the non-negotiable effects of a patient's bodily deterioration on their sense of self and, in so doing, offers a powerful new perspective on embodiment and emotion in death and dying." "A detailed and subtle ethnographic study, The Dying Process engages with a range of deeply complex and ethically contentious issues surrounding the care of dying patients in hospices and elsewhere. This book makes a significant contribution to the field of the sociology of the body and will also be an invaluable text for professionals, students and others who wish to enhance their understanding of hospice and palliative care."--Jacket